If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5r + -18r + -6 = 111 Reorder the terms: -6 + 5r + -18r = 111 Combine like terms: 5r + -18r = -13r -6 + -13r = 111 Solving -6 + -13r = 111 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -13r = 111 + 6 Combine like terms: -6 + 6 = 0 0 + -13r = 111 + 6 -13r = 111 + 6 Combine like terms: 111 + 6 = 117 -13r = 117 Divide each side by '-13'. r = -9 Simplifying r = -9
| 6=-7/9+v | | 33333333n=33333333 | | [8(z+4)-19]-2(z-3)+2= | | 1/5a-27=7 | | 5x+6+1=17 | | -16=-1+4n+1 | | 6+14=0 | | 9(2K+3)+2=11(K-k) | | 4x-8+4x=-16 | | 3b-3=4b+9 | | -4x-4=36 | | 12x/12=35/12 | | 9=2r-3+6 | | 2x+1=x+111 | | 2x+7=2x+5 | | (3x+2y-1)dx=(2x-3y+1)dy | | -11/9x3/10 | | 8s-10=27-(3s-7) | | x+4+6x=-3 | | 3x+10x-(5x+9)= | | 1/3a-2=15 | | 2h+5k-h+3k+4h= | | 2x=10x+21 | | 7x+3(-5+3)=-71 | | c/-3-1-2 | | k+1+4=5 | | -5y+10=10y | | (4/3)+(x/5)=(3x-5/6) | | x/6-x/2=-6 | | (2x+7)(2x^2+4x+4)= | | -5(-2-3z)= | | -6(2x+1)=-3x+7-9x |